ROBOTICS AS ONE OF THE DIRECTIONS OF STEM-EDUCATION IN THE NEW UKRAINIAN SCHOOL - Пукальський, Іван; Скрипничук, Наталія; Лусте, Ірина; Яшан, Богдан (SWorldJournal, 2022)
Features of the introduction of STEM education in the new Ukrainian school for students are investigated in this article. The purpose of STEM education in educational institutions is to clearly explain the necessary material to students, as well as to dev